2018
DOI: 10.1002/qj.3338
|View full text |Cite
|
Sign up to set email alerts
|

An intermediate‐complexity model for four‐dimensional variational data assimilation including moist processes

Abstract: This article presents a new Moist Atmosphere Dynamics Data Assimilation Model (MADDAM), an intermediate-complexity system for four-dimensional variational (4D-Var) data assimilation. The prognostic model equations simulate nonlinear moisture advection, precipitation, and the impact of condensational heating on circulation. The 4D-Var assimilation applies the incremental approach and uses transformed relative humidity as a control variable. In contrast to the model dynamical variables, which are analyzed in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Improvements in NWP in the Tropics can come from both advancements in model initialization and model development. More accurate initial states (analyses) are produced using new observations and improved data assimilation schemes (e.g., Žagar, 2004; Zaplotnik et al ., 2018). Current methodologies do not account sufficiently for EWs, which, together with sparse wind observations and deficient moist dynamics, lead to uncertainties in tropical analysis datasets (Podglajen et al ., 2014; Žagar et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in NWP in the Tropics can come from both advancements in model initialization and model development. More accurate initial states (analyses) are produced using new observations and improved data assimilation schemes (e.g., Žagar, 2004; Zaplotnik et al ., 2018). Current methodologies do not account sufficiently for EWs, which, together with sparse wind observations and deficient moist dynamics, lead to uncertainties in tropical analysis datasets (Podglajen et al ., 2014; Žagar et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These challenges motivated the present in‐depth investigation of the couplings between aerosols, moisture, and dynamical variables. For this purpose, we extended an intermediate‐complexity model MADDAM (Zaplotnik et al ., , ZZG18) using the aerosol prognostic equation, which represents the most dominant aerosol processes on the time‐scale of the typical assimilation window: advection and wet deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Zaplotnik et al . (), hereafter ZZG18, demonstrated that winds can also be retrieved from time series of moisture observations in perfect‐model 4D‐Var in the presence of a moisture sink in the form of a simple, flow‐convergence initiated precipitation process. In the case of linear flow, the observation spatial sampling was found to be more important than the observation update frequency, whereas for nonlinear flow the update frequency becomes crucial.…”
Section: Introductionmentioning
confidence: 99%
“…This is the "Hólm transform", which is used in the ECMWF 4D-Var system. It is also used, with adaptations, in HIRLAM (Gustafsson et al, 2011), in Met Office Var systems (Ingleby et al, 2013b), and in an intermediate research model (Zaplotnik et al, 2018). Since there is little literature on the Hólm transform itself, we provide some detail here.…”
Section: "Symmetrising" Transformsmentioning
confidence: 99%